2021
DOI: 10.11005/jbm.2021.28.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Bone Health in Men: A Systematic Review and Meta-Analysis

Abstract: Background Research on osteoporosis and physical activity often focuses on women. We aimed to conduct a systematic review to assess the benefits and harms of physical activity interventions for men’s bone health. Methods We used standard methods and searched for randomized controlled trials (RCTs) (duration, ≥6 months) published in all languages across multiple databases and trial registries. The last search was conducted on July 22, 2020. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
2
15
2
Order By: Relevance
“…Based on GRADE, it was concluded that further research is unlikely to change the direction of the effect (Supplementary Table 2). These findings are different to the recently published metaanalysis [51], however Ashe et. al.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on GRADE, it was concluded that further research is unlikely to change the direction of the effect (Supplementary Table 2). These findings are different to the recently published metaanalysis [51], however Ashe et. al.…”
Section: Discussioncontrasting
confidence: 99%
“…(5) Review articles, case reports, editorials, conference abstracts, and letters were not considered. (6) We also excluded studies with participants with pre-training exercise habits close to the volume and intensity applied by the intervention protocol.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Many guidelines on osteoporosis and fracture prevention consider physical exercise as the most effective non-pharmacologic agent for increasing bone strength and reducing falls (e.g., [1][2][3]). However, in contrast to female cohorts [4,5], evidence for a favorable effect of exercise on Bone Mineral Density (BMD) in men is still limited (review in [6][7][8][9]). Recently, two systematic reviews and meta-analyses of randomized controlled trials reported data on physical activity/exercise effects on BMD in men 18 years and older [6,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations